Training evaluation on the skill workshop program implemented by Enforcement Department towards enhancing employee performance in Kota Kinabalu City Hall / Claudia Bernard - Bernard, Claudia (Faculty of Business and Management, 2014)
Training plays an integral role in ensuring the employees have what it takes to perform their job. Therefore, Kota Kinabalu City Hall had allocated RM270 000 budget for training and development with hope that the training provided by Kota Kinabalu City Hall towards its employees could give higher return on investment to the organization. There are several training programs implemented inside the Enforcement Department which have never been evaluated before. Therefore, these studies conducted focusing on “Training Evaluation on the Skills Workshop Program Implemented by Enforcement Department towards Enhancing Employee Performance in Kota Kinabalu City Hall”. The main objective of this study is to determine the relationships between training reactions, learning outcomes and behavioral changes with employees’ performance in Kota Kinabalu City Hall. These three independent variables are from Kirkpatrick framework of evaluation. This study has been conducted within Kota Kinabalu City Hall and it involved 50 respondents from Enforcement Department of Kota Kinabalu City Hall. Result of the present study showed that all independent variables which is training reactions, learning outcomes and behavioral changes have significant relationship with employees’ performance. In addition, all the independent variables which is training reactions, learning outcomes and behavioral changes have positive relationship with employees’ performance.